DESCRIPTIVE ANALYSIS OF DECISION-MAKING CRITERIA FOR BUILDING RETROFIT CONSTRUCTION: A CASE STUDY OF BANGLADESH - Rumiko Sasaki; Tsuyoshi Seike; Yongsun Kim (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2018)
This paper is an exploratory study adopting a descriptive approach to clarify the background of technology adoption, role of multiple stakeholders, and decision-making processes in Bangladesh from the perspective of the possible technology dissemination. In addition, this study identifies the factors influencing decision-making on the basis of semi-structured interview in terms of frontend projects. In the retrofit process, assessments, standards, design policies, construction methods, and materials are mainly determined at the planning stage. International standards are a promoting factor in obtaining owner approval in technology selection, whereas cost and material procurement are the suppressing factors. The stakeholders in providing and diffusing new technology are technical consultants and structural designers, who are involved in the initial phase of the process. For technology diffusion within Bangladesh, these stakeholders must be acknowledged and worker education must be considered.